CO-DIAGENESIS OF IRON AND PHOSPHORUS IN HYDROTHERMAL SEDIMENTS FROM THE SOUTHERN EAST PACIFIC RISE: IMPLICATIONS FOR THE EVALUATION OF PALEOSEAWATER PHOSPHATE CONCENTRATIONS - Poulton S.W.; Canfield D.E. (My University, 2006)
We present a detailed study of the co-diagenesis of Fe and P in hydrothermal plume fallout sediments from ?19?S on the southern East Pacific Rise. Three distal sediment cores from 340-1130 km from the ridge crest, collected during DSDP Leg 92, were analysed for solid phase Fe and P associations using sequential chemical extraction techniques. The sediments at all sites are enriched in hydrothermal Fe (oxyhydr)oxides, but during diagenesis a large proportion of the primary ferrihydrite precipitates are transformed to the more stable mineral form of goethite and to a lesser extent to clay minerals, resulting in the release to solution of scavenged P. However, a significant proportion of this P is retained within the sediment, by incorporation into secondary goethite, by precipitation as authigenic apatite, and by readsorption to Fe (oxyhydr)oxides. Molar P/Fe ratios for these sediments are significantly lower than those measured in plume particles from more northern localities along the southern East Pacific Rise, and show a distinct downcore decrease to a depth of ?12 m. Molar P/Fe ratios are then relatively constant to a depth of ?35 m. The Fe and P speciation data indicate that diagenetic modification of the sediments is largely complete by a depth of 2.5 m, and thus depth trends in molar P/Fe ratios can not solely be explained by losses of P from the sediment by diffusion to the overlying water column during early diagenesis. Instead, these sediments are likely recording changes in dissolved P concentrations off the SEPR, possibly as a result of redistribution of nutrients in response to changes in oceanic circulation over the last 10 million years. Furthermore, the relatively low molar P/Fe ratios observed throughout these sediments are not necessarily solely due to losses of scavenged P by diffusion to the overlying water column during diagenesis, but may also reflect post-depositional oxidation of pyrite originating from the volatile-rich vents of the southern East Pacific Rise. This study suggests that the molar P/Fe ratio of oxic Fe-rich sediments may serve as a proxy of relative changes in paleoseawater phosphate concentrations, particularly if Fe sulfide minerals are not an important component during transport and deposition. ? 2006 Elsevier Inc. All rights reserved.
Keywords: APATITE; AUTHIGENIC MINERAL; CORE ANALYSIS; DIAGENESIS; DIFFUSION; GOETHITE; HYDROTHERMAL PLUME; IRON; PHOSPHORUS; SEDIMENT CHEMISTRY; EAST PACIFIC RISE; PACIFIC OCEAN